2011
DOI: 10.1007/s11896-010-9081-8
|View full text |Cite
|
Sign up to set email alerts
|

How Do Police Respond to Stalking? An Examination of the Risk Management Strategies and Tactics Used in a Specialized Anti-Stalking Law Enforcement Unit

Abstract: How do police respond to and manage complaints of stalking? To answer this question, we conducted a 3-phase study. First, we reviewed the literature to identify risk management tactics used to combat stalking. Second, we asked a group of police officers to review those tactics for completeness and group them into categories reflecting more general risk management strategies. The result was 22 categories of strategies. Finally, we used qualitative methods to evaluate the files of 32 cases referred to the specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 38 publications
(41 reference statements)
2
37
0
Order By: Relevance
“…Limited studies have examined police response to stalking (Brady & Nobles, 2017; Jasinski & Mustaine, 2001; Jordan et al, 2003; Storey & Hart, 2011; Tjaden & Thoennes, 2000) and have noted shortcomings. Police may not recognize stalking behavior or may not fully understand the statute guiding their jurisdiction (Lynch & Logan, 2015).…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%
“…Limited studies have examined police response to stalking (Brady & Nobles, 2017; Jasinski & Mustaine, 2001; Jordan et al, 2003; Storey & Hart, 2011; Tjaden & Thoennes, 2000) and have noted shortcomings. Police may not recognize stalking behavior or may not fully understand the statute guiding their jurisdiction (Lynch & Logan, 2015).…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%
“…The complex and chronic nature of stalking behaviour was highlighted by a recent study investigating the risk assessment strategies of specialist Canadian police officers. Storey and Hart () found that a wide range of tactics were employed by the police, the victims, and others involved (median 19, range 1–52) in an attempt to stop the stalking behaviour. Furthermore, there was no relationship between the number of tactics employed and the perceived risk to victims.…”
Section: Introductionmentioning
confidence: 99%
“… In a more recent study (Storey & Hart, in press), the SAM was employed in an examination of police management tactics in 32 stalking cases. The results showed good to moderate interrater reliability across the three SAM domains: intraclass correlation coefficients (ICC 1 ) were 0.91, 0.92, and 0.72, respectively, for the nature, perpetrator, and victim vulnerability factors. …”
mentioning
confidence: 99%